2019
DOI: 10.1371/journal.pone.0220962
|View full text |Cite
|
Sign up to set email alerts
|

Posturographic characteristics of the standing posture and the effects of the treatment of obesity on obese young women

Abstract: To determine the impact of body weight on quiet standing postural sway characteristics in young women, this research compared spontaneous oscillations of the center of foot pressure (COP) between 32 obese (BMI: 36.4 ± 5.2 kg/m 2 ), and 26 normal-weight (BMI: 21.4 ± 1.5 kg/m 2 ) women and assessed the influence of obesity treatment and body weight reduction on postural sway. Trajectories of the COP were assessed while the subjects were standing quietly with eyes ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
(91 reference statements)
0
15
1
Order By: Relevance
“…These unique for MS changes could be also observed in Sway Vector azimuth (SVaz). This pattern of changes is different from normal, age-matched, healthy adults (Błaszczyk and Cie sli nska-Swider, 2019;Cie sli nska-Swider and Błaszczyk, 2019).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…These unique for MS changes could be also observed in Sway Vector azimuth (SVaz). This pattern of changes is different from normal, age-matched, healthy adults (Błaszczyk and Cie sli nska-Swider, 2019;Cie sli nska-Swider and Błaszczyk, 2019).…”
Section: Discussioncontrasting
confidence: 69%
“…Redundancy and interaction of proprioceptive, visual, vestibular systems ensure erect posture stability while the postural sway does not interfere with the control. In young healthy adults, even turning off the visual input does not interfere with the postural control ( Błaszczyk and Cieślińska-Świder, 2019 ; Cieślińska-Świder and Błaszczyk, 2019 ). Eyes closure results in a limited and statistically insignificant increase of postural sway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with abdominal obesity seem to exhibit greater postural instability in comparison with women with gynoid fat distribution. In another study conducted by the same authors [8] on young obese women, they found that participants exhibited sagittal plane postural instability only with their eyes closed. After body weight reduction, ML static stability decreased, directly connected to a change in the base of support.…”
Section: Femalesmentioning
confidence: 92%
“…This multimodal (integrating visual, vestibular, and proprioceptive inputs) and redundant control causes chaotic center of mass (CoM) oscillations known as postural sway [6][7][8]. In clinics the quality and integrity of balance control is generally assessed using various measures of postural sway [6].…”
Section: Introductionmentioning
confidence: 99%